Climate Change, Collective Action, and Women's Assets - International Food Policy Research Institute (2011)
The "Enhancing Women's Assets to Manage Risk under Climate Change: Potential for Group-Based Approaches" project explores ways to contribute to poverty reduction in Sub-Saharan Africa and South Asia (especially Bangladesh, Ethiopia, Kenya, and Mali) through helping poor women farmers and pastoralists manage risks and adapt to climate change as a result of more effective programs to protect or strengthen women's control over critical assets, including natural and social capital, and/or increased returns to those assets. The project is supported by the Federal Ministry for Economic Cooperation and Development, Germany.